On the problem of currency control in Kazakhstan in the Customs Union. (Journal of actual problems of jurisprudence, 2016)
This article discusses some of the issues of currency controls related to the functioning of the Customs Union and the unification of the currency legislation. In the context of globalization and integrationnecessary developing methods of foreign exchange controls to curb illegal export of capital from the country.